Evaluation of Marketing Strategy for Jungle Gold Chocolate Products Using the Internal-External (IE) Matrix Approach - Gustiana Istita, Nelly; Djohanputro, Bramantyo; Denny Tewu, ML. (JURNAL MANAJEMEN MOTIVASI, 2026)
The chocolate industry is shifting toward sustainable and plant-based products amid supply volatility. This study evaluates Jungle Gold’s marketing strategy using the IE Matrix. Based on differentiation and value-based marketing theory, a descriptive quantitative approach was applied using IFE and EFE matrices. The results show strong product differentiation but weaknesses in pricing, capacity, and distribution. External opportunities exist, but threats remain significant. The IFE score of 2.82 and EFE score of 2.74 place the firm in a hold and maintain position. The strategy is relevant but requires improvement in digital marketing, distribution, and cost efficiency. Keywords: Marketing Strategy, IE Matrix, Plant-Based Chocolate